Особливості інституційного забезпечення розвитку малих форм аграрного виробництва України - Гривківська, О. В.; Збарський, В. К.; Терещенко, Максим Анатолійович; Hryvkivska, O.; Zbarskyi, V.; Tereshchenko, Maksym (Мелітополь : 2021, 2021)
UA: В статті досліджено теоретичні аспекти інституційного забезпечення розвитку аграрного сектору національної економіки, а саме в системі малих форм виробництва сільськогосподарської продукції. Доведено важливість розвитку інституційного середовища як невід’ємної складової ефективної економічної діяльності сучасного підприємницького середовища. Проаналізовано особливості функціонування даної складової аграрного виробництва як сукупності різновекторних форм господарювання. Обґрунтовано необхідність диференційованого підходу щодо аналізу рівня результативності їхньої діяльності з урахуванням соціальноекономічних принципів розвитку. Проведено дослідження інституційного забезпечення функціонування малих форм аграрного виробництва як системи взаємопов’язаних складових. Доведено важливість стимулювання розвитку сімейно-трудових форм аграрного підприємництва як засобу позитивного впливу на питання продовольчої безпеки, а також соціально-економічні процеси в системі сільських територій. Сформульовано напрями розвитку інституційного середовища в системі малих форм аграрного виробництва України. EN: Introduction. The current stage of development of the national agricultural sector is characterized by the growing importance of small forms of production. It should be noted that their impact is not only on purely economic processes. However, it should be noted that the specifics of today's realities imply the need to adapt small businesses to the principles of the model of post-industrial economy, as on this basis is the functioning of all components of the economic mechanism of the world's leading countries. Its characteristic features, among other things, are the strengthening of the role of the information component in the system of economic relations, as well as the presence of an institutional environment, elements of which are public organizations, the media, local authorities and others. The nature of the influence of the institutional environment on the current state and the specifics of the functioning of small forms of agricultural production determined the relevance of the chosen topic, purpose and direction of the study. The purpose of this article is to study the theoretical and methodological aspects of institutional support for the functioning of small forms of agricultural production in Ukraine. Results. The study proved the need for a differentiated approach to the analysis of small forms of agricultural production. A comparative analysis of the institutional essence of farms, households and personal farms. The system of institutional support for the development of small forms ofagricultural production is analyzed. Conclusions. The article analyzes the theoretical foundations of institutional support for the functioning of small forms of agricultural production in Ukraine. The importance of the development of the institutional environment as an integral part of effective economic activity of the modern business environment is substantiated. The directions of development of the institutional environment in the system of small forms of agricultural production of Ukraine are formulated. The importance of the information component as an important factor in ensuring the competitive operation of peasant farms is emphasized.
Features of institutional support for the development of small forms of agricultural production of Ukraine
Keywords: інститут; інституційне середовище; ефективність; селянське господарство; аграрне виробництво; фермерське господарство; institute; institutional environment; efficiency; peasant economy; agricultural production; farm